Comparative study of sample preparation procedures to determine the main compounds in ayahuasca beverages by QuEChERS and high‐performance liquid chromatography analysis - Gonçalves, Joana (2024)
Introduction Ayahuasca is a psychoactive drink originally consumed by indigenous people of the Amazon. The lack of regulation of this drink leads to uncontrolled consumption, and it is often consumed in religious contexts. Objective The aim of this work is to compare three miniaturised extraction techniques for extracting the main ayahuasca compounds from beverages. Methodology Three sample pretreatment techniques were evaluated (dispersive liquid–liquid microextraction [DLLME], microextraction by packed sorbent [MEPS] and QuEChERS [Quick, Easy, Cheap, Effective, Rugged and Safe]) for the simultaneous extraction of N,N-dimethyltryptamine (DMT), tetrahydroharmine (THH), harmine, harmaline, harmol and harmalol from ayahuasca beverage samples. Then, the most promising technique (QuEChERS) was chosen to pre-concentrate the analytes, subsequently detected by high-performance liquid chromatography coupled to a diode array detector (HPLC-DAD). Results The procedure was optimised, with the final conditions being 500 μL of extractor solvent, 85 mg of primary secondary amine (PSA) and 4 s of vortexing. The analytical method was validated, showing to be linear between 0.16 and 10 μg/mL for β-carbolines and between 0.016 and 1 μg/mL for DMT, with coefficients of determination (R2) between 0.9968 and 0.9993. The limit of detection (LOD) and lower limit of quantification (LLOQ) were 0.16 μg/mL for all compounds, except for DMT (0.016 μg/mL) and extraction efficiencies varied between 60.2% and 88.0%. Conclusion The analytical methodology proved to be accurate and precise, with good linearity, LODs and LLOQs. This method has been fully validated and successfully applied to ayahuasca beverage samples.